2013
DOI: 10.1039/c3fd00057e
|View full text |Cite
|
Sign up to set email alerts
|

Liposome and protein based stealth nanoparticles

Abstract: Liposomes and protein based nanoparticles were tuned with different polymers and glycolipids to improve stealth and thus decrease their clearance by macrophages. Liposomes were coated with polyethylene glycol (PEG) and brain-tissue-derived monosialoganglioside (GM1). Bovine serum albumin (BSA) nanoparticles were produced incorporating a PEGylated surfactant (PEG-surfactant). All obtained nanoparticles were monodisperse, with sizes ranging from 80 to 120 nm, with a zeta-potential close to zero. The presented st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…More recently, some studies have suggested a "dysopsonization" phenomenon where PEG actually promotes binding of certain proteins that then act to mask the vehicle [28]. We recently demonstrated a reduction in internalization of PEGylated nanoparticles by activated RES macrophages [29]. We showed that by increasing PEG concentration from 5 to 10%, the stealth degree of nanoparticles clearly improved, as the internalization of nanoparticles by macrophages is greatly reduced, which is consistent with the current scaling models for polymers at interfaces.…”
Section: Polyethylene Glycolsupporting
confidence: 65%
“…More recently, some studies have suggested a "dysopsonization" phenomenon where PEG actually promotes binding of certain proteins that then act to mask the vehicle [28]. We recently demonstrated a reduction in internalization of PEGylated nanoparticles by activated RES macrophages [29]. We showed that by increasing PEG concentration from 5 to 10%, the stealth degree of nanoparticles clearly improved, as the internalization of nanoparticles by macrophages is greatly reduced, which is consistent with the current scaling models for polymers at interfaces.…”
Section: Polyethylene Glycolsupporting
confidence: 65%
“…The characterization of these protein nanoemulsions is presented in Table 2 and is in line with what was previously described by our group, demonstrating that the particles are small, neutral surface (zeta-potential close to zero) and present high stability along time. 21 All these results establish that these PEGylated protein nanoemulsions have suitable characteristics required for systemic administration. Nanoemulsions containing imaging and targeting agents were prepared by introducing of BSA-FITC and BSA-FA conjugate in aqueous phase of initial formulation (Table 1).…”
Section: Fa-tagged Protein Nanoemulsions and Specific Uptake By Fr Pomentioning
confidence: 84%
“…Nanoemulsions were produced by high pressure homogenization of an aqueous phase (BSA solution containing a PEGylated surfactant and BSA-FA conjugate) with an organic phase (vegetable oil). Small, stable, PEGylated (described elsewhere 21 ) and FA-functionalized nanoemulsions were obtained and evaluated in terms of specific uptake using a lymphoma cell line (A20 cell line). The biological effect of the nanoemulsions loaded with CORM-2 was tested both in vitro and in vivo.…”
mentioning
confidence: 99%
“…The DOPE-containing liposomes formulation is used to stabilize the bilayer form through the addition of a cleavable lipid derivative of polyethylene glycol (DSPE-MPEG). This new nanobiodevice has been developed by UMINHO and tested by other partners and seems to be the best candidate to be used [3]. Approximately a duration of 1 hour 30 minutes is required to produce liquid suspension of 15 mL containing nanoliposomes with a liposomal formulation DOPE/CH/DSPE-MPEG concentration of 11.9 mM at the purification step.…”
Section: Measurement Strategymentioning
confidence: 99%
“…Moreover, the two abovementioned factors exposure and hazards are still rather poorly understood in the context of nanosuspensions [3]. Nanosuspensions are biphasic systems consisting of pure drug particles (or nanostructured vesicles like liposomes) dispersed in an aqueous solvent, stabilized by surfactants.…”
Section: Introductionmentioning
confidence: 99%